2009
DOI: 10.1016/j.jpubeco.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-primary education on primary school performance

Abstract: Although the theoretical case for universal pre-primary education is strong, the empirical foundation is weak. In this paper, we contribute to the empirical case by investigating the effect of a large expansion of universal pre-primary education on subsequent primary school performance in Argentina. We estimate that one year of preprimary school increases average third grade test scores by 8 percent of a mean or by 23 percent of the standard deviation of the distribution of test scores. We also find that prepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
159
0
23

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(193 citation statements)
references
References 27 publications
11
159
0
23
Order By: Relevance
“…Bernal and Keane (2010) provide a thoughtful discussion of the most problematic issues in the estimation of childcare effects on children's outcome and present the different approaches that have been taken by previous literature using American data, including family fixed-effects (see for example Blau, 1999) and instrumental variable estimation (see Bernal and Keane, 2011). Recently, Berlinski et al (2009) The first strand of literature is based on some ad hoc studies, where pre-school children were recruited and followed for a number of years. In the US, the NICHD Study of Early Child Care was initiated in 1991 and included 1,300 children followed up to their seventh year of school.…”
Section: Overview Of Existing Literaturementioning
confidence: 99%
“…Bernal and Keane (2010) provide a thoughtful discussion of the most problematic issues in the estimation of childcare effects on children's outcome and present the different approaches that have been taken by previous literature using American data, including family fixed-effects (see for example Blau, 1999) and instrumental variable estimation (see Bernal and Keane, 2011). Recently, Berlinski et al (2009) The first strand of literature is based on some ad hoc studies, where pre-school children were recruited and followed for a number of years. In the US, the NICHD Study of Early Child Care was initiated in 1991 and included 1,300 children followed up to their seventh year of school.…”
Section: Overview Of Existing Literaturementioning
confidence: 99%
“…Four studies used difference-in-differences or fixed effect designs [14,[17][18][19] to estimate an ITT effect of daycare on maternal outcomes. Angeles and colleagues [14] used a fixed effects design and compared mothers with children on daycare waiting lists to those attending the same daycares in the same locality and found differences in maternal employment and hours worked per month, but no impacts on income or measures of mental health.…”
Section: Resultsmentioning
confidence: 99%
“…In Argentina, following an expansion in public preschool provision between 1993 and 1999, a study found that an additional year of preschool increases third grade language and mathematics test scores by 0.23 standard deviations, with larger effects for children living in poor areas [8]. The expansion also led to improved attention, effort, class participation, and discipline among children who had the opportunity to attend preschool.…”
Section: Medium-term Studies Following Children Into Their School Yearsmentioning
confidence: 99%